Biomass Carbon and Nitrogen allocation in different tree species: do tree compartments and size affect C:N relationship? - Sione, Silvana María José; Ledesma, Silvia Gabriela; Aceñolaza, Pablo Gilberto; Wilson, Marcelo German (Finnish Society of Forest Science, 2023)
Tree carbon (C) and nitrogen (N) concentrations and C:N ratio are critical for understanding the elemental compositions of forests, N use efficiency, productivity and the biogeochemical cycles. We evaluate differences in C and N allocation among biomass compartments of three N‑fixing tree species of Espinal Argentine eco-region; the scaling relationship between C and N and the C:N ratio variation among compartments and tree size. Neltuma affinis (Spreng.) C.E. Hughes & G.P. Lewis, Neltuma nigra (Griseb.) C.E. Hughes & G.P. Lewis and Vachellia caven (Molina) Seigler & Ebinger plants (n = 30 for each species) were felled, grouped by stem basal diameter-based size classes and partitioned into 3 biomass compartments: stem (st), large branches (lb) and small branches + leaves, flowers and fruits (sbl). C and N concentrations were markedly influenced by species and biomass compartments. In general, sbl compartment presented more N than the st and lb, while C concentrations in Neltuma stems were the highest. Overall, no isometric C–N scaling relationships were found in different compartments. C:N variations in compartments were positively correlated with N concentrations but did not exhibit any significant association with C concentrations. C:N ratios differed significantly among species and biomass compartments. The C:N ratio for compartments ranked in an order of st > lb > sbl. C:N ratio variability in sbl was the least. Only in N. affinis and V. caven stems C:N relationship differed among tree size. Our results provide evidence of the importance of using in situ C and N concentration per main tree species and biomass compartments, to more accurate estimates of C and N stocks.